GAYA PENGASUHAN ORANGTUA UNTUK KESEHATAN INNER CHILD ANAK - Putri, Ellyana Ilsan Eka; Damayanti, Annisa; Andriani, Viena Wanidha (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
The background in encouraging this research is the amount of violence experienced by children due to parenting styles. If there is no good relationship in the family, children tend to be timid and shy because they rarely pay attention to their opinions. Memories of children that he considered bad in childhood will affect his life when he grows up when he experiences inner child. This research aims to provide readers with an understanding of the parenting style of parents and children and the inner child's influence on the sustainability of their development so that parents can be better at educating their children so that they do not cause prolonged injuries to them until they are brought up to adulthood. The data collection technique used in this study is a literature study in which the data comes from books, scientific journals, literature that is worthy of being used as a source for research that the author will examine. The results of the study show that parenting consists of 3 types, one of which is authoritarian parenting where parents demand children to follow the rules without asking the child's opinion, this makes children tend to be insecure.